Purinergic signaling: A new front-line determinant of resistance and susceptibility in leishmaniasis - Mariana Chaves (Biomedical Journal, 2022)
Leishmaniasis is a neglected tropical disease that causes several clinical manifestations. Parasites of the genus Leishmania cause this disease. Spread across five continents, leishmaniasis is a particular public health problem in developing countries. Leishmania infects phagocytic cells such as macrophages, where it induces adenosine triphosphate (ATP) release at the time of infection. ATP activates purinergic receptors in the cell membranes of infected cells and promotes parasite control by inducing leukotriene B4 release and NLRP3 inflammasome activation. Moreover, uridine triphosphate induces ATP release, exacerbating the immune response. However, ATP may also undergo catalysis by ectonucleotidases present in the parasite membrane, generating adenosine, which activates P1 receptors and induces the production of anti-inflammatory molecules such as prostaglandin E2 and IL-10. These mechanisms culminate in Leishmania's survival. Thus, how Leishmania handles extracellular nucleotides and the activation of purinergic receptors determines the control or the dissemination of the disease.